Periodismo ciudadano versus Periodismo profesional: ¿somos todos periodistas? - Real Rodríguez, Elena; Príncipe Hermoso, Sergio; Agudiez Calvo, Pinar (Estudios sobre el Mensaje Periodístico, 2007)
The important role that Internet has received in the society and the wide interactivity that grants to its protagonists has provoked that everybody who celebrates the excellence and virtues of Network think that each actor participating in the communicational process of this electronic media must be considered as a journalist, simply by the mere fact of becoming active agents able to spread information to a great audience, and, consequently, to compare this activity with the one that is developed by journalistic information professionals. In this way, “Citizen Journalism” arises as an alternative and as a clear opposition to the traditional Journalism which seems to have lost the monopoly of the information. But, is it really possible to consider every one as journalist?